On the origin and development of an editorial, political and collective gesture: Journal of Psychology - Third Era - Alessandroni, Nicolás (Facultad de Psicología (Universidad Nacional de La Plata, Argentina), 2017)
The Director and Editor-in-Chief of the Journal of Psychology, Nicolás Alessandroni, presents the new guidelines of the publication and its editorial and political bases. The main novelties of this new era of the Journal of Psychology are listed.